2020
DOI: 10.1016/j.gfs.2020.100409
|View full text |Cite
|
Sign up to set email alerts
|

Rising concerns over agricultural production as COVID-19 spreads: Lessons from China

Abstract: There are rising concerns over the impact of COVID-19 on the agricultural production, which may become a nonnegligible threat to the long-term food supply and food security. This paper discusses the impact of COVID-19 on agricultural production in China, followed by government responses to alleviate the negative effects. The results show that unreasonable restrictions would block the outflow channels of agricultural products, hinder necessary production inputs, destroy production cycles, and finally undermine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(197 citation statements)
references
References 8 publications
6
191
0
Order By: Relevance
“…This lockdown time coincided with harvesting operations of Rabi/winter season crop and sowing time of Zaid/summer season crops. Globally, there are rising concerns over the impact of COVID-19 on agricultural production (Pu and Zhong 2020 ). However, in India, a large number of initiatives were taken to ease the situation (Nayyar 2020 ; Padhee and Pingali 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This lockdown time coincided with harvesting operations of Rabi/winter season crop and sowing time of Zaid/summer season crops. Globally, there are rising concerns over the impact of COVID-19 on agricultural production (Pu and Zhong 2020 ). However, in India, a large number of initiatives were taken to ease the situation (Nayyar 2020 ; Padhee and Pingali 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few of the recent researches have tried to analyze the implications of COVID-19 pandemics on agricultural productions and supply chain globally (Pu & Zhong, 2020;Kumar, Padhee, & Kumar, 2020;Gillespie, 2020;Galanakis, 2020;Singh & Neog, 2020;Solomon, Pratap, & Swapna, 2020;Weersink, von Massow, & McDougall, 2020;Sharma, Talan, & Jain, 2020;Zhang et al, 2020). Pu and Zhong (2020) argued that unreasonable restrictions would block the outflow channels of agricultural products, hinder necessary production inputs, destroy production cycles, and finally undermine production capacity and suggested that there is a need to ensure effective logistics for agricultural products, ensure effective supply of critical inputs, provide various supports to agricultural production and farmers and make use of innovative methods to promote sales such as e-tailing. Kumar et al (2020) argued that the vulnerabilities in agricultural supply chains and depleted workforces caused by the COVID-19 crisis have hurt farms of all sizes in India.…”
Section: Introductionmentioning
confidence: 99%
“…As a means to document the existing situation in the agricultural sector, predicting the potential effects of the COVID-19 pandemic and suggesting measures to mitigate them, several studies have been conducted. Some of them analyzed solely the impact of the virus on agricultural production regarding the first infected by COVID-19 countries, namely China [18,19] and later Italy [7,[20][21][22]. In contrast, some studies dealt with the agricultural sector of countries, which were later infected by the viral pandemic, including countries from the rest of Asia (India [23,24] and Iran [25]), Oceania (Australia [26] and New Zealand [27]), Europe (rest of EU [5,28] and the United Kingdom (UK) [29]) as well as America (Argentine [30], Peru [31], Canada [32][33][34][35][36] and the US [14,37,38]).…”
Section: Pandemic Effects On Agriculutral Sectormentioning
confidence: 99%